Innovative IPV from attenuated Sabin poliovirus or newly designed alternative seed strains. (November 2012) - Hamidi, Ahd; Bakker, Wilfried AM
This article gives an overview of the patent literature related to innovative inactivated polio vaccine (i-IPV) based on using Sabin poliovirus strains and newly developed alternative recombinant poliovirus strains. This innovative approach for IPV manufacturing is considered to attribute to the requirement for affordable IPV in the post-polio-eradication era, which is on the horizon. Although IPV is a well-established vaccine, the number of patent applications in this field was seen to have significantly increased in the past decade. Currently, regular IPV appears to be too expensive for universal use. Future affordability may be achieved by using alternative cell lines, alternative virus seed strains, improved and optimized processes, dose sparing, or the use of adjuvants. A relatively short-term option to achieve cost–price reduction is to work on regular IPV, using wild-type poliovirus strains, or on Sabin-IPV, based on using attenuated poliovirus strains. This price reduction can be achieved by introducing efficiency in processing. There are also multiple opportunities to work on dose sparing, for example, by using adjuvants or fractional doses. Renewed interest in this field was clearly reflected in the number and diversity of patent applications. In a later stage, several innovative approaches may become even more attractive, for example the use of recombinant virus strains or even a totally synthetic vaccine. Currently, such work is mainly carried out by research institutes and universities and therefore clinical data are not available.